Seated saline infusion test in predicting subtype diagnosis of primary aldosteronism. (6th November 2019) - Kaneko, Hiroki; Umakoshi, Hironobu; Ishihara, Yuki; Sugawa, Taku; Nanba, Kazutaka; Tsuiki, Mika; Kusakabe, Toru; Satoh‐Asahara, Noriko; Yasoda, Akihiro; Tagami, Tetsuya
Abstract: Context: Although saline infusion test is widely used as a confirmatory test for primary aldosteronism (PA), it is reportedly less sensitive in patients in whom aldosterone is responsive to the upright position by performing it in recumbent position. Based on a single‐centre experience, seated saline infusion test (SSIT) has been reported to be highly sensitive and superior to recumbent testing in identifying both unilateral and bilateral forms of PA. However, due to limited participants number, the utility of SSIT needs to be validated in other series. Objective: This study aimed to evaluate the accuracy of SSIT in determining the PA subtypes compared with adrenocorticotropic hormone stimulation test under dexamethasone suppression (Dex‐AT). Patients and Setting: Sixty‐four patients with PA who underwent both SSIT and Dex‐AT were included. Subtype diagnosis of PA was determined by adrenal venous sampling (AVS) (16 unilateral and 48 bilateral forms). Main Outcome Measure: Plasma aldosterone concentrations (PACs) were measured after SSIT and Dex‐AT. Results: The area under the receiver operating characteristic (ROC) curve for diagnosing unilateral PA was greater in SSIT than that in Dex‐AT (0.907 vs. 0.755; P = .023). ROC curve analysis predicted optimal cut‐off PACs of 13.1 ng/dL (sensitivity, 93.8%; specificity, 79.2%) for SSIT and 34.2 ng/dL (sensitivity, 75.0%; specificity, 68.8%) for Dex‐AT. Conclusions: Seated saline infusion test has superior accuracy in subtype diagnosis of PA compared with Dex‐AT. SSIT can be a sensitive test for determining patients who require AVS prior to surgery.